Considerations and Factors Affecting the Impartiality of the Disciplinary Investigator: A Comparative Study - Flayyih Hasan, Assist. Lect. Suhair (Basra studies journal, 2025)
Impartiality is a fundamental attribute that must be present in the individual conducting a disciplinary investigation. This individual must act free from any personal inclinations when handling the case and avoid any conduct that suggests favoritism, discrimination, or bias. Their judgment should be issued independently, unaffected by personal whims, ideologies, or beliefs—whether religious, political, or partisan. However, the impartiality of a disciplinary investigator is not always guaranteed. Personal motives and objectives that diverge from the public interest may influence their conduct, for various reasons and considerations. This can lead to deviation in the imposition of disciplinary sanctions against the employee under investigation. Therefore, it is essential to establish mechanisms that safeguard impartiality and prevent it from being left to the investigator’s sole discretion. The researcher divided this study into three sections, concluding with a set of findings and recommendations. Chief among these is the need to amend the current Law of Discipline for State Employees in Iraq to include explicit provisions stipulating grounds for disqualifying and recusing members of investigative committees, instead of relying on the application of the Civil Procedure Law. It also recommends stipulating that members of these committees must hold higher administrative grades than the employee under investigation